High accuracy of recombinant fusion protein early secretory antigenic target protein 6‐culture filtrate protein 10 skin test for the detection of tuberculosis infection: a phase III, multi‐centered, double‐blind, hospital‐based, randomized controlled trial. (January 2023) - Xia, Lu; Xu, Miao; Li, Feng; Li, Tao; Yang, Heng; Wang, Weihua; Wu, Qi; Li, Youlun; Chen, Xiaohong; Ou, Qinfang; Chu, Naihui; Pan, Hongqiu; et al.
Highlights: Early secretory antigenic target protein 6-culture filtrate protein 10 (EC) skin test is a phase III clinical trial. We validated its accuracy for tuberculosis infection. We identified that the immune state was associated with the diagnostic accuracy of EC skin test. This study enriches the clinical evidence in related EC-based skin tests. Abstract : Objectives: To verify the diagnostic utility of recombinant fusion protein ESAT6-CPF10 (EC), a novel skin test reagent to detect Mycobacterium tuberculosis infection. Methods: A multi-centered, double-blind, randomized controlled trial was conducted from December 17, 2015, to March 2, 2018. Participants involved in this study included those with active tuberculosis (TB), suspected pulmonary TB, or non-TB pulmonary disease. Each participant received three tests simultaneously, TB-specific enzyme-linked immunospot assay (T-SPOT.TB), tuberculin skin test (TST), and EC skin test (ECST), and adverse events were reported. Results: Diagnostic accuracy was analyzed using data from 1085 protocol-compliant participants. The sensitivities of the ECST, TST, and T-SPOT.TB were 91.2% (95% CI, 89.0-93.2%), 91.4% (95% CI, 89.1-93.3%), and 92.1% (95% CI, 89.9-93.9%), respectively. The specificities of the ECST (69.7%, 95% CI, 64.5-74.5%) and T-SPOT.TB (76.1%, 95% CI, 71.2-80.5%) were significantly higher than the TST (54.4%, 95% CI, 48.9-59.7%). The agreements between ECST and TST (kappa = 0.632) and between ECST and T-SPOT.TB (kappa = 0.780) were substantial. No severe adverse event was reported. Conclusion: The diagnostic performance of the ECST was close to the T-SPOT.TB assay in the detection of TB infection and indicated good potential for clinical application in common scenarios.